Smart mirror enhancement with RFID - Mohd Isham, Muhammad Faris; Mohd Aman, Azana Hafizah; Mahmod Attar Bashi, Zainab Senan; Jalil, Mohamad Sirajuddin; E. Altaleb, Abdulazeez (UKM Press, 2024)
Since it was first presented a few years ago, smart mirrors have gained popularity as an indoor convenience. When the idea of smart homes started to be raised by different parties in earlier years, a variety of smart devices were released and distributed worldwide. The introduction of smart devices into several outdoor industries shows that their application is not limited to the indoors. Therefore, this project focuses on solving problems for industries, i.e. the clothing sales industry. Smart Mirror is an innovative device that combines information technology with traditional mirrors, giving users access to important information in an interactive way. The project was developed using the Raspberry Pi 4 as the main controller and MagicMirror2 software as an interface platform. This Smart Mirror displays information such as weather, news, and notifications on a digital display hidden behind a mirrored glass. The project also uses an RFID scanner for displaying clothing information with RFID tags, as well as voice control via a microphone for easy user interaction. Users can access information through a digital display, view clothing information with RFID tags, and interact with the system via voice. Future enhancements to the project are possible, including integrating artificial intelligence and new functional modules. This Smart Mirror can significantly improve daily life and information monitoring using technology and creativity.